Impact of body weight on virological and immunological responses to efavirenz-containing regimens in HIV-infected, treatment-naive adults. (14th January 2015) - Marzolini, Catia; Sabin, Caroline; Raffi, François; Siccardi, Marco; Mussini, Cristina; Launay, Odile; Burger, David; Roca, Bernardino; Fehr, Jan; Bonora, Stefano; Mocroft, Amanda; Obel, Niels; et al.
<x xml:space="preserve">Abstract</x> Objective: The prevalence of overweight and obesity is increasing among HIV-infected patients. Whether standard antiretroviral drug dosage is adequate in heavy individuals remains unresolved. We assessed the virological and immunological responses to initial efavirenz (EFV)-containing regimens in heavy compared to normal-weight HIV-infected patients. Design: Observational European cohort collaboration study. Methods: Eligible patients were antiretroviral-naïve with documented weight prior to EFV start and follow-up viral loads after treatment initiation. Cox regression analyses evaluated the association between weight and time to first undetectable viral load (<50 copies/ml) after treatment initiation, and time to viral load rebound (two consecutive viral load >50 copies/ml) after initial suppression over 5 years of follow-up. Recovery of CD4+ cell count was evaluated 6 and 12 months after EFV initiation. Analyses were stratified by weight (kg) group (I – <55; II – >55, <80 (reference); III – >80, <85; IV – >85, <90; V – >90, <95; VI – >95). Results: The study included 19 968 patients, of whom 9.1, 68.3, 9.1, 5.8, 3.5, and 4.3% were in weight groups I–VI, respectively. Overall, 81.1% patients attained virological suppression, of whom 34.1% subsequently experienced viral load rebound. After multiple adjustments, no statistical difference was observed in time to undetectable viral load and virological rebound for heavier individuals compared to their normal-weight counterparts. Although heaviest individuals had significantly higher CD4+ cell count at baseline, CD4+ cell recovery at 6 and 12 months after EFV initiation was comparable to normal-weight individuals. Conclusion: Virological and immunological responses to initial EFV-containing regimens were not impaired in heavy individuals, suggesting that the standard 600 mg EFV dosage is appropriate across a wide weight range. Video Abstract: http://links.lww.com/QAD/A635